Manajemen Madrasah Ibtidaiyah dalam Meningkatkan Mutu Lulusan - Ahmad Gawdy Prananosa; Donni Pestalozi; M Rusni Eka Putra; Rudi Erwandi (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study was to determine madrasa management in improving the quality of graduates. This study uses a qualitative approach with phenomenological methods. This research was conducted in Madrasah Ibtidaiyah Assidiq Giriyoso, Jayaloka District, Musi Rawas Regency. Data collection techniques consist of observation, interviews, and documentation. The data analysis technique uses the Miles & Huberman interactive model, with the following stages: data collection, data reduction, data display, and conclusion or verification (conclusion drawing & verifying). The results show that Madrasahs have planned a tahfiz qur'an program by preparing supporting facilities such as tahfiz huts in front of the class, educators, and education staff who are fluent and memorize the Koran, the curriculum listed in the learning implementation plan, then establish good relations with the community. especially in supporting the tahfiz al-qur'an program. In conclusion, Madrasah Ibtidaiyah Giriyoso has planned, organized, implemented, evaluated the tahfiz and English programs in improving the quality of graduates. Keywords: Management, Madrasah Ibtidaiyah, Quality of Graduates